FIELD COMPARISON OF TWO KINDS OF CHARCOAL TUBES FOR SAMPLING AROMATIC HYDROCARBONS (TOLUENE & XYLENE) IN A PAINT FACTORY - P .Nassiri; F. Golbabai; A. Barzegar (Tehran University of Medical Sciences, 1996)
In order to evaluate the effectiveness of the Iranian made charcoal tubes in the field , 60 local made and 60 imported ones (SKC type) were randomly selected and placed side by side for sampling aromatic hydrocarbons (including Benzene, Toluene, Xylene) in workers breathing zone in a paint factory. The results indicated that there were no statistically significant differences between the mean concentrations of aromatic hydrocarbons measured in studied groups. The ratios of pressure drop to flow rate of Iranian made tubes were statistically higher than the SKC ones (P<0.0l).